The Pol Pot regime : race, power, and genocide in Cambodia under the Khmer Rouge, 1975-79 - Kiernan, Ben (Yale University Press, 2008)
This edition of Ben Kiernan's account of the Cambodian revolution and genocide includes a new preface that takes the story up to 2008 and the UN-sponsored Khmer Rouge tribunal. Kiernan's other books include 'Blood and Soil: A World History of Genocide and Extermination from Sparta to Darfur' and 'How Pol Pot Came to Power'.
Keywords: Parti communiste du Kampuchea.; Pol Pot.; Pol, Pot; Parti communiste du Kampuchea; Cambodia -- Politics and government -- 1975-1979.; Communism -- Cambodia.; Political atrocities -- Cambodia.; Genocide -- Cambodia.; Cambodge -- Politique et gouvernement -- 1975-1979.; Atrocités politiques -- Cambodge.; HISTORY.; HISTORY -- Asia -- Southeast Asia.; Communism; Genocide; Political atrocities; Politics and government; Cambodia; 1975-1979